In‐pixel temperature sensor for high‐luminance active matrix micro‐light‐emitting diode display using low‐temperature polycrystalline silicon and oxide thin‐film‐transistors. Issue 6 (26th May 2020) - Chen, Yuanfeng; Lee, Suhui; Kim, Hyunho; Lee, Jiseob; Geng, Di; Jang, Jin
Abstract: We propose an in‐pixel temperature sensor using low‐temperature polycrystalline silicon and oxide (LTPO) thin‐film transistor (TFTs) for high‐luminance active matrix (AM) micro‐light‐emitting diode (LED) displays. By taking advantage of the different off‐current characteristics of p‐type LTPS TFTs and n‐type a‐IGZO TFTs under temperature change, we designed and fabricated a temperature sensor consists of only LTPO TFTs without additional sensing component or material. The fabricated sensor exhibits excellent temperature sensitivity of up to 71.8 mV/°C. In addition, a 64 × 64 temperature sensor array with 3T sensing pixel and integrated gate driver has also been fabricated, which demonstrates potential approach for maxing out the performance of high‐luminance AM micro‐LED display with real‐time in‐pixel temperature monitoring. Abstract : The authors propose an in‐pixel temperature sensor using only LTPO TFTs for high‐luminance AM micro‐LED displays. The fabricated sensor exhibits excellent temperature sensitivity of up to 71.8 mV/°C. In addition, a 64 × 64 sensor array demonstrates potential approach for maxing out the performance of high‐luminance AM micro‐LED display with real‐time in‐pixel temperature monitoring.